2018
DOI: 10.18632/oncotarget.25275
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes/vessel-associated mural cells (VAMCs) are the major source of key epithelial-mesenchymal transition (EMT) factors SLUG and TWIST in human glioma

Abstract: Epithelial-to-mesenchymal transition (EMT) is supposed to be responsible for increased invasion and metastases in epithelial cancer cells. The activation of EMT genes has further been proposed to be important in the process of malignant transformation of primary CNS tumors. Since the cellular source and clinical impact of EMT factors in primary CNS tumors still remain unclear, we aimed at deciphering their distribution in vivo and clinico-pathological relevance in human gliomas.We investigated 350 glioma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…Besides enhancing adhesion to the substrate, pericytes inhibit intercellular adhesions and expression of E-cadherin, conferring breast cancer cells a migratory, invasive phenotype, characteristic of cells undergoing epithelial-to-mesenchymal transition (EMT) [36]. In line with these results, pericytes have been shown to be major sources of EMT factors in glioma [37]. We have also found that pericytes have a prompt effect on the proliferation of TNBC, but not of melanoma cells.…”
Section: Discussionsupporting
confidence: 71%
“…Besides enhancing adhesion to the substrate, pericytes inhibit intercellular adhesions and expression of E-cadherin, conferring breast cancer cells a migratory, invasive phenotype, characteristic of cells undergoing epithelial-to-mesenchymal transition (EMT) [36]. In line with these results, pericytes have been shown to be major sources of EMT factors in glioma [37]. We have also found that pericytes have a prompt effect on the proliferation of TNBC, but not of melanoma cells.…”
Section: Discussionsupporting
confidence: 71%
“…[5–10] Previous analysis of different mRNA signatures of GBM led to the proposition of a new stratification of GBM subgroups, in which the mesenchymal mRNA signature profile has been associated with more frequent recurrences and higher malignancy. [11] More recent studies showed that the rather more benign pilocytic astrocytoma (World Health Organization, WHO grade I) also displayed a mesenchymal signature,[12] which at least partly contradicts the hypothesis that, in glioma, the mesenchymal signature is associated with increased malignancy. [13] A possible reason for the correlation of the mesenchymal signature with a poor prognosis might be that the EMT factor expression in glioma was analysed at the mRNA level [14] instead of determining protein levels and identifying the cell type that expresses specific EMT proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The specific phenomenon that P75CUX1 significantly regulated the migration and invasion but not the proliferation of glioma cells facilitated us to reveal novel mechanisms of rapid infiltrating progression in glioma. The mechanism of correlation of CUX1 and EMT was the breakthrough finding because EMT is a well-recognized mechanism in glioma diffuse infiltration 12 14 . In our study, when P75CUX1 was knocked down, E-cadherin, ZO-1, and Claudin were significantly augmented while N-cadherin, β-catenin, Slug, Snail, MMP2, and MMP9 were reduced in vitro and in vivo, indicating a more epithelial phenotype under P75CUX1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In glioma, epithelial–mesenchymal transition (EMT) has an essential role in diffuse infiltrating phenotype and frequently associated with glioma recurrence and malignant development 5 , 6 , 12 14 . EMT is an important biological process for epithelial-derived malignant tumor cells to acquire the ability to migrate and invade 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation